Development and standardization of the Dot Blot test for serological diagnosis of bovine leptospirosis (Research, Society and Development, 2021)
Leptospirosis a public health problem and an endemic zoonosis in Brazil, is diagnosed by serological methods. Therefore, low-cost and easy to execute methodologies with good/high sensitivity, such as Dot Blot, are an important diagnostic tool. The aim of this study was to standardize and validation the dot-blot technique for the serological diagnosis of bovine leptospirosis. Several concentrations of antigens applied to nitrocellulose membranes, and different dilutions of conjugated bovine serum were evaluated to develop and standardize the test. The best distinction/contrast between positive and negative samples was observed for 1μL antigen (0.11μg/μL outer membrane protein of the Hardjo serovar (OMPH) and 0.08 μg/μL outer membrane protein of the Wolffi serovar (OMPW)), 1:500 and 1:10000 bovine serum dilution and conjugate, respectively. The Dot Blot test efficiency was 71.87% and kappa index, 0.46 (p